Legal Protection for Consumers in Online Transactions: A Case Study of Marketplace Platforms in Indonesia - Harry Tuhumury (Leges Privatae, 2025)
The development of digital technology has driven the rapid growth of online transactions in Indonesia, particularly through marketplace platforms such as Tokopedia, Shopee, and Bukalapak. Ease of access and broad market reach are accompanied by various legal issues, such as goods not as described, late delivery, fraud, and personal data leaks. This study aims to analyze the effectiveness of legal protection for consumers in online transactions, using a normative juridical approach that examines laws and regulations, internal marketplace policies, and case studies of actual disputes. Data were obtained from primary legal materials (UUPK, UU ITE, PP No. 80 of 2019, Permendag No. 50 of 2020, Law on Personal Data Protection), secondary legal materials, and tertiary legal materials. The results show that the national legal framework is normatively adequate, but its implementation is hampered by weak supervision, differences in policies between platforms, imbalanced consumer bargaining power, low legal literacy, and limited access to external dispute resolution mechanisms. The discussion reveals that consumer protection relies more on internal platform policies than on the direct implementation of national regulations. In conclusion, standardization of consumer protection policies across all marketplaces, strengthening of substantive government oversight, integration of personal data protection, and increasing consumer legal literacy are needed to build a safe, fair, and just online transaction ecosystem.